Further optical properties of CdX (X¼ S, Te) compounds under quantum dot diameter effect: Ab initio method - Yarub, Al - Douri; Baaziz, H.; Charifi, Z.; Khenata, R.; Uda, Hashim, Prof. Dr.; Al-Jassim, M. (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/